Optimization of ultrasound assisted extraction using response surface methodology for estimation of Pterostilbene in Pterocarpus marsupium - Kanchan Dilip Nikam, Sachin Shivling Bhusari, Pravin Shridhar Wakte (Journal of Applied Pharmaceutical Science, 2023)
Pterostilbene (PTB) is an active component of Pterocarpus marsupium which is a well-known source for its therapeutic effects. The current study optimized the ultrasound-assisted extraction conditions to maximize the amount of PTB extracted from P. marsupium and its estimation by High-performance liquid chromatography. The response surface methodology (RSM) was employed to determine the solvent: solid ratio (A), soaking time (B), and sonication time (C). To determine the optimal processing conditions, the experiment’s design and data analysis employed a Box Behnken Design. The optimal conditions for ultrasound-assisted extraction include a solvent-to-solvent ratio of 10:1 v/w, a soaking time of 20 minutes, and a sonication time of 10 minutes. Under these circumstances, PTB experimental yield was 2.14 mg/g, which was significantly close to the predicted values of 2.070 mg/g. The experimental results were consistent with those anticipated by RSM models.
Keywords: Ultrasound assisted extraction, Pterostilbene, Pterocarpus marsupium, response surface methodology, HPLC